Persistent lipid abnormalities in statin-treated patients with diabetes mellitus in Europe and Canada: results of the Dyslipidaemia International Study - Leiter, Lawrence; Lundman, P.; Silva, P. M. da; Drexel, H.; Jünger, C.; Gitt, Anselm Kai (Diabetic medicine, 2011)
Diabet. Med. 28, 1343-1351 (2011) - - Abstract - Aim To assess the prevalence of persistent lipid abnormalities in statin-treated patients with diabetes with and without the metabolic syndrome.